Meningkatkan Minat Belajar dan Kemampuan Kognitif Anak Usia Dini Melalui Penerapan Model Pembelajaran Area - Amperawati, Lilis; Umi Harti; Umilia; Durrotul Muniroh; Usup; Yunaini; Nita Priyanti (LP. Ma'arif Janggan Magetan, 2023)
The success of an early childhood education institution is determined by the learning model used, because through an appropriate learning model, appropriate efforts can be made to stimulate the development and growth of children. One of the learning models that we know is the area learning model.RA Raudhatul Ummah is an early childhood education unit located in Bekasi City. In the 2021-2022 school year, they will start using the area learning model, it is hoped that this model can increase children's interest in learning according to the desired choice. The study was conducted on 15 students in class B1 and 14 in class B2. using descriptive qualitative method and carried out for 1 months. Data collection was done through observation, interviews and viewing of children's portfolio documentation. To get valid data, the researcher uses data triangulation theory by involving research subjects, namely key informants, main informants and supporting informants. The results showed that there was a significant change and increase in the development of children's interest in mathematical cognitive abilities which reached the end of 86,2%.